Pathfinders : Navigating the twilight years. - Chua, Alvin. (2008)
ACCOMPANIED BY: FEATURE WRITING (HARDCOPY) – PLEASE APPROACH ACRC LOAN COUNTER. An illustrative feature about how the elderly in Singapore have overcome stereotypes, showing how the ageing process can actually be a new path of purpose and fulfillment.